Tracking the journey: Europium-doped polystyrene nanoplastics distribution in a model invertebrate (terrestrial isopod, Porcellio scaber, Crustacea) upon dietary exposure - Sara Novak; Anita Jemec Kokalj; Gregor Marolt; Jernej Imperl; Rok Kostanjšek; Andraž Dolar; Laura J. Zantis; Willie Peijnenburg; Thijs Bosker; Matej Hočevar; Valentina Perc; Špela Saje; et al. (Ecotoxicology and Environmental Safety)
Knowing the fate of nanoplastics in organisms is indispensable to assess the risk of these persistent environmental pollutants. We designed an in-depth study on the biodistribution of metal (europium)-doped polystyrene nanoparticles (EuPSs) in terrestrial isopods (Crustacea, Porcellio scaber) upon dietary exposure. Biodistribution of two types of spherical EuPSs, 100 nm and 300 nm, with similar Eu content and negligible dissolution of Eu ions in deionized water, was investigated. In the first step, the total Eu concentration in different body regions (gut, digestive glands and rest of the body) was measured with inductively coupled plasma mass spectrometry (ICP-MS). Next, tissue localisation of the particles was analysed using X-ray microtomography, fluorescent microscopy and laser ablation ICP-MS. In addition, scanning electron microscopy was used to check the presence of the particles in the digestive system. As the measured levels of Eu in body parts other than the gut, including the digestive gland, are negligibly low, we conclude that EuPSs do not accumulate in the body of P. scaber following dietary exposure. Based on our findings, we recommend complementing analytical and microscopic techniques with detailed physiological and anatomical knowledge of the investigated organisms before drawing any conclusions on body distribution.